2002
DOI: 10.1108/02637470210444259
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term impact of flooding on residential property values

Abstract: Current planning schemes in Australia identify areas that are potentially flood liable. This identification of flood liable land is based on flood height levels over time. Throughout New South Wales this measure of flood affectation is determined by three classifications. These classifications also influence the development of residential property within these flood areas.Prospective purchasers are advised of this flood zoning when a full title search is carried out. However, as these properties are often loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The more recent studies carried out by Lamond and Proverbs (2006), Lamond et al (2007) Eves and Brown (2002) and Eves (2004b in the UK have shown that a flood will have its greatest impact on a residential property market in the first 12 months after the flood event but differences in prices between flooded and nonflooded properties would reduce over time and after 3 to 4 years of no further flooding house prices tend to be similar. Lamond et al (2005) have also carried out comparative research of floods and housing markets in the US.…”
Section: Floods and Property Marketsmentioning
confidence: 99%
“…The more recent studies carried out by Lamond and Proverbs (2006), Lamond et al (2007) Eves and Brown (2002) and Eves (2004b in the UK have shown that a flood will have its greatest impact on a residential property market in the first 12 months after the flood event but differences in prices between flooded and nonflooded properties would reduce over time and after 3 to 4 years of no further flooding house prices tend to be similar. Lamond et al (2005) have also carried out comparative research of floods and housing markets in the US.…”
Section: Floods and Property Marketsmentioning
confidence: 99%
“…Owned by the government Drought: 1/9 large utilities reported major impact; additional 2/9 of them reported moderate impact; 4/10 small utilities reported moderate impact. Flood: 2/9 large utilities reported major impact; additional 5/9 of them reported moderate impact; 6/10 small utilities reported major impact; additional 4/10 of them reported moderate impact Eves & Brown (2002), England Effect of floods and flood damage on residential property prices across counties after the floodings in Autumns 1998 and 2000; floods are categorised as regular, 1 in I. premium > 10% for property close to river/coastline, if no flood potential; discount < 10%, if flood potential (discounts reported in only three counties of 23); II. The impact of the flooding of 2000/2001 on property prices (discount) was reported as follows: 0: 8 counties; <5%: 10 counties; 5-10%: 6 counties; 10-20%: 6 counties; >20% (severe 33 50 years and 1 in 100 years; areas may be prone to inland/river or coastal/tidal flooding; questionnaire to 51 Charted Surveyors to identify flood-prone areas flooding): 4 counties.…”
Section: Logarithmicmentioning
confidence: 99%
“…The impact of the flooding of 2000/2001 on property prices (discount) was reported as follows: 0: 8 counties; <5%: 10 counties; 5-10%: 6 counties; 10-20%: 6 counties; >20% (severe 33 50 years and 1 in 100 years; areas may be prone to inland/river or coastal/tidal flooding; questionnaire to 51 Charted Surveyors to identify flood-prone areas flooding): 4 counties. Eves (2002), Sydney, Australia;1984-2000 the long term processes related to the flooding problem; to identify areas that are potentially liable to flooding, using planning schemes; in New South Wales three classifications of flood-height levels => residential development; house sales: flood-prone ~ flood-free areas: flood liability is reported by local government; data (44 streets): 22 street flood prone ~22 streets flood-free in lower market area detached single-family or low rise medium density residential complexes total: 1067 fl. free + 923 fl.…”
Section: Logarithmicmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the impact is observed from the size of the coefficients of the time dummy variables. Such studied events include natural disasters (Eves 2002;Holway and Burby 1990;Murdoch et al 1993) and environmental pollution (Bible et al 2002;Gamble and Downing 1982;Reichert 1997). The adverse impacts of disasters or pollution are expected to exert a long lasting negative impact on property prices.…”
Section: Literature Reviewmentioning
confidence: 99%